Unveiling Emerging Interdisciplinary Research Challenges in the Highly Threatened Sclerophyllous Forests of Central Chile - Zorondo-Rodriguez, F (BioMed Central Ltd, 2024)
Background: The potential ecosystem collapse of forests in Mediterranean-type ecosystems (MTEs) by unprecedented droughts is worrisome due to the impacts on its exceptional biodiversity and human well-being. However, research integrating the impacts of global change drivers, forest resilience and the challenges facing human-nature relationships is still scarce. Methods and results: Using the central Chile megadrought and recently massive forest browning event as a model scenario, we identified, through a scientific literature review and an interdisciplinary scientific workshop, the research priorities and questions to address for MTEs in a context of global change. Our results highlighted knowledge gaps that need to be covered, particularly in social and environmental sciences, with an emphasis on soil science. Research priorities must focus on (1) the understanding of interactive effects of global and local anthropogenic drivers on MTEs and (2) the evaluation of the potential impacts of MTEs collapse on human well-being and ecosystem functioning. Conclusions: We highlight the need for a collaborative approach involving scientists, landowners, managers/administrators, and policymakers to apply adaptive forest management against the current socio-environmental challenges under a global change context. © The Author(s) 2024.